Effects of Marine-Derived Components on Cardiovascular Disease Risk Factors and Gut Microbiota Diversity - Ingrid Lamminpää; Amedeo Amedei; Cinzia Parolini (Marine Drugs)
Cardiovascular diseases (CVDs), which comprise coronary heart disease, hypertension, and stroke, collectively represent the number one cause of death globally. Atherosclerosis is the dominant cause of CVDs, and its risk factors are elevated levels of low-density lipoprotein cholesterol and triglycerides, hypertension, cigarette smoking, obesity, and diabetes mellitus. In addition, diverse evidence highlights the role played by inflammation and clonal haematopoiesis, eventually leading to immunity involvement. The human microbiota project and subsequent studies using next-generation sequencing technology have indicated that thousands of different microbial species are present in the human gut. Disturbances in the gut microbiota (GM) composition, i.e., gut dysbiosis, have been associated with diseases ranging from localised gastrointestinal disorders to metabolic and cardiovascular illnesses. Of note, experimental studies suggested that GM, host immune cells, and marine-derived ingredients work together to ensure intestinal wall integrity. This review discusses current evidence concerning the links among GM, marine-derived ingredients, and human inflammatory disease. In detail, we summarise the impact of fish-derived proteins/peptides and algae components on CVD risk factors and gut microbiome. Furthermore, we describe the interplay among these dietary components, probiotics/prebiotics, and CVDs.